MODEL DINAMIK PENGELOLAAN SUMBERDAYA LAHAN DI KOTA BANDAR LAMPUNG - Dear Mapala Simarmata; Abdullah Aman Damai; Bambang Utoyo Sutiyoso; Teguh Endaryanto; Maulana Muklis; Muhammad Irfan Affandi (Forestry Study Program University Of Mataram, 2023)
The rate of population growth has an impact on the carrying capacity of the environment because the need for land is directly proportional to the increase in population growth, so land conversion can occur. The population growth rate of Bandar Lampung City reached 2.70% with a population in 2020 reaching 1,166,066 people and a built-up area of ​​9,920 hectares. The purpose of this study is to build a dynamic model of land resources in Bandar Lampung City by presenting a land suitability map for Bandar Lampung City, making a dynamic system analysis model for land resources and recommending policies for sustainable land resource management in Bandar Lampung City. The tools used are Stella, Acrgis and AHP (Analytical Hierarchy Process) applications. Based on land capability analysis, Bandar Lampung City has sufficient development capability. Based on the results of the AHP, the environmental aspect is a priority aspect in land resource management that supports sustainable development with an eigenvalue of 0.53 and the selection of scenario 1 is to maintain a protected area/limit with an eigenvalue of 0.56. The model is built from three sub-models, namely population sub-model, land use sub-model and economic sub-model. The model is validated by comparing the actual value and the simulated value. Statistical testing was carried out using the t-test with an acceptable deviation limit of 5%. The results of the scenario 1 simulation show that current resource management can still guarantee an increase in the built-up land for the next 20 years of simulation, but this must be followed by the addition of green open space (RTH) results. The need for green space must be met to support the balance with the built area. To maintain protected areas, namely implementing the fulfillment of green open space needs.